USING MODULAR EDUCATIONAL TECHNOLOGY IN CHEMISTRY - I. X. Ruziyev; E. Yu. Ergashev (European Science Publishing, 2024)
This work presents material on the use of modular teaching technology in chemistry. Developmental technologies arouse students' interest in science, help activate educational and cognitive activities that help creative perception and assimilation of knowledge. The transition to developmental educational technologies makes the student not only a self-educated subject, but also one who knows the mechanism of self-education, is interested in self-development, and ensures that he becomes a capable person. Science teachers can use this material to create a modular science program.
Keywords: modular training, educational technology, interactive training, chemical education, pedagogical modular, training modules, individualization of training, active learning methods, independent work of students, effectiveness of training, distance education, problem-based education, chemistry teaching methodology, development of critical thinking, academic achievements.